Ectopic thyroid and Hashimoto's thyroiditis arising from a thyroglossal duct cyst: a case report. - Gök, Uzeyir; Keleş, Erol; Cobanoglu, Bengü; Yildiz, Mücahit; Dönder, Emir (My University, 2003)
A seventy-five-year-old male patient presented with a palpable smooth mass that moved upwards on swallowing, extending from the hyoid bone to the cricoid cartilage. Ultrasonography, scintigraphy, and thyroid hormone measurements showed the mass free from the thyroid gland. Following a diagnosis of infected thyroglossal duct cyst by fine needle aspiration biopsy, the mass was removed by surgery. Histopathologic diagnosis was Hashimoto's thyroiditis that developed from the ectopic thyroid tissue on the wall of thyroglossal duct cyst.
Keywords: Aged; Choristoma; Diagnosis, Differential; Humans; Male; Thyroglossal Cyst; Thyroid Gland; Thyroiditis, Autoimmune; aged; article; autoimmune thyroiditis; case report; choristoma; differential diagnosis; human; male; pathology; thyroglossal duct cyst; thyroid gland